Implementation of Traditional Malay Design Values in Contemporary Malay Houses (International Journal of Built Environment and Sustainability, 2016)
Traditional houses are the most essential architectural experience that is in harmony with the people's culture, beliefs, environment and lifestyles. The development of design values in contemporary architecture by tracking traditional design values in architecture paves the way for arguments concerning the implementation of authentic Malay traditional house design values in contemporary Malay houses. In addition, it is hypothesized that the Malay traditional houses theoretically provide a constructive innovative framework for the design performance of the contemporary Malay house. In this research, data was compiled through field observation and documentary review. The evidence revealed that Malay traditional houses convey a concrete message of richness encompassing architectural design values and theoretical propositions. The credibility of the results was improved and confirmed by a confluence of evidence via a confirmation process. The findings suggested that there is a rich source of subjective support, lending proof to the premise of the research investigation. The research has highlighted the significance of traditional architectural design values towards innovative design in the architecture of contemporary Malay houses as a workable pattern for use in the design of contemporary architecture.